Carotenogenesis of five strains of the algae Dunaliellasp. (Chlorophyceae) isolated from Venezuelan hypersaline lagoons. - Guevara, Miguel (2005)
We evaluated discontinuous cultures (Algal medium at 0.5 mM of NaNO3, and 27% NaCl) of five strains of Dunaliella sp. isolated from Venezuelan hypersaline lagoons (Araya, Coche, Peonía, Cumaraguas, and Boca Chica) and one strain from a reference collection (Dunaliella salina, LB1644). Cultures were maintained to 25±1 °C, with constant aeration, photoperiod 12:12, and two light intensities (195 and 390 μE.m-2.s-1) during 30 days. Cell count was recorded on a daily basis using a Neubaüer camera. Totals of chlorophyll a and carotenoids were measured at the end of the experiment. The largest cellular densities were measured during the smallest light intensities. The strain with the largest cellular density was isolated from Boca Chica (8 x106 and 2.5 x106 cel.ml-1 a 390 and 195μE.m-2.s-1, respectively). The increment of light intensity produced a significant reduction of growth rates in all strains. Totals of carotenoids by volume were as large as 390 μE.m-2.s-1. Strains LB1644, from Coche and Araya were those that produced the largest amount of carotenoids (38.4; 32.8 and 21.0 μg.ml-1, respectively). Differences total carotenoids by cell between treatments were significant. The largest concentration was 390 μE.m-2.s-1. The strains LB1644 and Coche produced the highest values of carotenes (137.14 and 106.06 pg.cel-1, respectively). Differences in the relation carotenoid:chlorophyll a between the strains at various light intensities was significant. Strains LB1644 presented the largest value of the relation carotenoids:chlorophyll a (20:1) at 195 μE.m-2.s-1. No significant differences were detected in the strain Coche (15:1). All the other strains showed relations lower than one. Our results suggest that the strains of Coche and Araya show potential to be used in the biotechnology of carotenoids production.